Applying a Lesson Plan for a Digital Classroom: Challenges and Benefits - Sugianto, Ahmad (International Journal of English Education and Linguistics (IJoEEL), 2020)
A lesson plan is one of the essential parts that may lead English teachers to gain the expected learning outcome. Nevertheless, to implement the lesson plan so that the expected outcome can be met might be challenging if conducted in a digital classroom. This study was aimed to unravel the way a lesson plan was implemented in a digital classroom. A case study was employed and the collected data from interview, classroom observation, and document were analysed through an interactive model. Findings revealed that both strength and weakness as a result of implementing the lesson plan for a digital classroom were perceived by the subjects. This study reached a conclusion that the lesson plan was categorised as good, i.e. it conforms 86.9% to the components of the curriculum 2013. Moreover, the challenges consisted of the aspects of the network connection, preparation, and students’ familiarity with the use of the technology; meanwhile, the benefits covered the aspects of the resources, students’ skills and participation, and efficiency.